BINARY PATRIARCHY IN NIKAH SIRI: An Ecofeminism Perspective - Aisyah Arsyad (JICSA : Journal of Islamic Civilization in Southeast Asian, 2018)
Nikah Siri (unregistered, or ‘secret’ marriage) has increased in Indonesia since the passing of marriage law No. 1/1974, one article of which required the registration of all marriages. Meanwhile, under Islamic law (fikih munakahat), registration was not one of the pillars of marriage. The 1974 state law provides for penalties for persons involved in unregistered marriages such as nikah siri: on the other hand, under Islamic law nikah siri was considered as marriage, as the terms and the pillars of marriage were fulfilled, even without registration. Religious and state law are clearly at odds as far as marriage registration is concerned.Gradually, Nikah Siri has led to various forms of social problems such as nikah siri online, falsification of documents, and  even human trafficking. The main problem which is one focus of this research is the negative impact of nikah siri on women and children. Not having an official marriage registration document creates difficulties for women and children which affects their future life opportunities, as with children not being accepted for schooling, as one example. One significant legal ruling discussed has implications for this social deprivation of women and children but not to the extent expected to date.By using the concepts of dualism from ecofeminism theory (perspective) to analyse the role of patriarchy in creating and perpetuating gender inequality in the case of nikah siri, the writer argues that Islamic marriage law - as it has developed in Indonesia -  is still dominated by patriarchal values and, as such, impacts negatively on women and children. The stereotype of istri siri is proven in that the hierarchical dualism that underlies patriarchal structures and thinking, is placing women in a subordinate position. Patriarchal interpretations of Islamic law have put many women in a position where they regard nikah siri as the best option for themselves, although such marriages in fact place them in a precarious position legally and socially, and lead to an imbalance of power both between themselves and the men they marry, and any other legal wives of that man.